Wholesale Prices in the United States, 1825-45 - Cole, Arthur H. (The Review of Economics and Statistics, 1926)
THE investigation of wholesale prices in the United States for the period I825-45, here described, was undertaken with a dual purpose. First, there was need for a more complete account of the movements in individual and general prices for the period before the Civil War than had been given. The available series of annual index numbers, of course, gave no information of the movements of average prices during the year. Moreover, the diversity of movement among the prices of individual commodities, the variation in movement between groups of commodities economically allied,